Detection of toxic metal ions Pb2+ in water using SiO2@Au core-shell nanostructures: A simple technique for water quality monitoring - Daware, Krishna; Kasture, Manasi; Kalubarme, Ramchandra; Shinde, Rakesh; Patil, Kashinath; Suzuki, Norihiro; Terashima, Chiaki; Gosavi, Suresh; Fujishim, Akira (Chemical Physics Letters, 2019)
The present paper demonstrates a development of simple, sensitive and selective optical probe for detection of Pb2+ ions in water using monodispersed silica-gold core-shell nanostructures (SiO2@Au NSs). Structural and elemental analysis confirms the phase purity of nanostructures. The SPR studies for SiO2 @Au NSs reveals, linear dynamic range for Pb2+ ions detection, in the concentration range of 100 ppb to 2 ppm, with detection limit of 100 ppb, which is 5 times higher than AuNPs. Cross sensitivity study confirm its selectivity towards Pb2+ ions over other metal ions. XPS analysis shows the interaction of Pb2+ ions with core-shell NPs.